The Effect of Mathematical Logical Intelligence on Mathematical Problem Solving Ability through Contextual Approach - Noor, Naili Luma'ati; Kori'ah, Siti (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
The purpose of this study was to prove that there is a correlation between mathematical logical intelligence and mathematical problem solving ability through a contextual approach and to prove that is a significant effect of mathematical logical intelligence on mathematical problem solving ability through a contextual approach. The sample used was 31 students of class VIII B MTs Tauhidiyah Sulang with the material used is polyhedron. The learning process in this study was based on lesson plans with a contextual approach, while the data were obtained through mathematical logical intelligence instruments and mathematical problem solving ability tests. After the data was collected and analyzed using two techniques, namely simple linear correlation and simple linear regression, the conclusions were: 1) There is a positive correlation and significant (r = 0.417) between mathematical logical intelligence and problem solving ability through a contextual approach. 2) There is a significant effect of mathematical logical intelligence on mathematical problem solving ability through a contextual approach of 17.4% which is explained by the regression line equation Y=3.360+0.265X, which means that the mathematical problem solving ability variable has a consistent value a 3.360 and it can be said that for every increase 1 unit of mathematical logical intelligence value increase 0.265 trought contextual approach.